Design of a Controlled-Release Delivery Composite of Antibacterial Agent Gatifloxacin by Spherical Silica Nanocarrier - Guo, Xueping; Mo, Wenjing; Zhang, Dingyang; Wang, Yurong; Cao, Fang; Zhai, Tianyun; Rao, Wenhua; Guan, Xiong; Xu, Lei; Pan, Xiaohong (Frontiers in Chemistry, 2022)
In this study, a spherical silica nanoparticle was explored as a gatifloxacin carrier which was synthesized by chemical precipitation method. It was found that there was no new chemical bond formation during the loading process between gatifloxacin and silica, which implying that the binding was driven by physical interaction. In addition, the drug loading and encapsulation efficiency could be improved by appropriately increasing the content of nano-silica in the loading process. Meanwhile, the release rate of gatifloxacin after loading nano-silica was also improved, suggesting the successfully designed of a controlled-release delivery composite. The silica nanocarrier could significantly improve the antibacterial performance of Escherichia coli by 2.1 times, which was higher than the pure gatifloxacin, and the 24 h bacteriostatic rate was higher than that of a simple mixture of silica nanoparticles and gatifloxacin. Strong reactive oxygen species (ROS) in GAT-SiO2 NPs suggests that ROS might be associated with bactericidal activity, the synergy between the physicochemical effect and ROS production of this material is proposed as the mechanism of its antibacterial activity, which can also be confirmed by the cell membrane damage observed under electron microscopy and DNA damage experiments. Collectively, our finding indicates that nano-silica microspheres could serve as a promising carrier for the sustained release of gatifloxacin thereby providing a new carrier design scheme for improvement of antibacterial effect.